2020
DOI: 10.1097/rlu.0000000000003081
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Colon Carcinoma Related to High Uptake in 18F-PSMA-1007 PET

Abstract: We present a 78-year-old man with suspicion of prostate cancer due to a PSA of 200 ng/mL, who underwent 18F-PSMA-1007 (prostate specific membrane antigen) PET/CT for primary staging. Besides heterogeneous uptake to the prostate, an increased PSMA uptake in the cecum was observed, located in the thickened cecal wall with suspicion of a secondary malignancy. Colonoscopic biopsy followed by hemicolectomy confirmed the diagnosis of colon adenocarcinoma. This case demonstrates the importance of bioptic workup of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This includes incidental findings and studies with a large number of patients. In four (suspected) prostate cancer patients, colorectal cancer was unexpectedly found, with an SUV max varying from 7.4 to 19.6 [ 13 , 14 , 15 , 27 ]. A second study, including metastatic colorectal cancer patients, found a mean SUV max in three patients for the primary tumor of 7.9 ± 2.5 (using [ 68 Ga]Ga-PSMA-11) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes incidental findings and studies with a large number of patients. In four (suspected) prostate cancer patients, colorectal cancer was unexpectedly found, with an SUV max varying from 7.4 to 19.6 [ 13 , 14 , 15 , 27 ]. A second study, including metastatic colorectal cancer patients, found a mean SUV max in three patients for the primary tumor of 7.9 ± 2.5 (using [ 68 Ga]Ga-PSMA-11) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also relevant for exploring the potential use of PSMA for diagnosis and theranostics of different neoplasms. In fact, an increasing number of manuscripts have discussed the possible use of radiolabeled PSMA imaging or treatment of colorectal cancer [3,7,8], brain tumors [4,9,10], women's and men's breast cancer [11,12], head and neck cancer [5] and other solid tumors. Few isolated reports have also documented the uptake of radiolabeled PSMA in lymphomas [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…6 There are multiple case reports showing PSMA uptake in benign tumors and nonprostate malignancies. [7][8][9][10][11][12][13] Desmoid-type fibromatosis, also known as aggressive fibromatosis, musculoaponeurotic fibromatosis, and desmoid tumor, is a rare mesenchymal neoplasm associated with high rates of local recurrence but lacks the potential to metastasize. 14 The treatment consensus has changed over the past decade from surgery to observation, and hence imaging plays an important role in follow-up.…”
mentioning
confidence: 99%
“…PSMA is also expressed in several other malignancies including breast, lung, colorectal, bladder, renal, pancreatic, and primary brain tumors 6. There are multiple case reports showing PSMA uptake in benign tumors and nonprostate malignancies [7][8][9][10][11][12][13]. Desmoid-type fibromatosis, also known as aggressive fibromatosis, musculoaponeurotic fibromatosis, and desmoid tumor, is a rare mesenchymal neoplasm associated with high rates of local recurrence but lacks the potential to metastasize 14.…”
mentioning
confidence: 99%